Understanding vaccine hesitancy through the lens of trust and the 3C model: evidence from Chinese General Social Survey 2021 - Dong, Bo; Xu, Hengxuan; Qi, Yuantao; Li, Yifan (Frontiers in Public Health, 2025)
BackgroundTrust is critical in managing infectious disease outbreaks, influencing both healthcare delivery and public compliance. While existing studies suggest trust reduces vaccine hesitancy (VH), the mechanisms remain unclear, particularly how different types of trust impact VH.MethodsThis study uses data from the 2021 Chinese General Social Survey (CGSS), analyzing responses from 7,907 individuals. VH was assessed via COVID-19 vaccination status. Four trust types—generalized, government, doctor, and internet trust—were examined using binary probit regression. Structural equation modeling analyzed the mediating role of psychological factors: self-confidence, complacency, and responsibility. Robustness checks employed alternative dependent variables and models.ResultsTrust exerts a significant negative predictive effect on vaccine hesitancy, suggesting that higher levels reduce the likelihood of vaccine hesitancy. This finding remains statistically significant after robustness tests. However, trust in the government and physician exert a greater influence on vaccine hesitancy than generalized trust and online trust. The three psychological antecedents—confidence, complacency, and collective responsibility—serve a crucial mediating role between trust and vaccine hesitancy. Most vaccinations were community-organized, followed by voluntary and employer-organized vaccination. Higher VH correlated with lower trust across all types, though most hesitancy levels occurred among those with moderate to high trust.ConclusionStrengthening trust—especially in government and healthcare providers—is essential to reducing VH. Psychological determinants like confidence, complacency, and responsibility play key roles in vaccination decisions. Tackling VH requires multi-level strategies: fostering public trust, enhancing government transparency, empowering healthcare professionals, combating online misinformation, and leveraging community initiatives.